Development Strategy for Hybrid Duck Farming in Besuki District Situbondo Regency - Prasetyo, Anang Febri; Pratama, Priandana Riardy Andrid; Dewi, Aryanti Candra; Subagja, Hariadi; Asrianto, Noor (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aims to analyze the right development strategy for the hybrid duck farming business in Besuki District and to find out how the influence of internal and external factors on the development of hybrid duck farming business in Besuki District. This study uses a descriptive research design by using questionnaires of the respondents. The data obtained were then analyzed using the IFAS matrix, EFAS matrix, SWOT diagram, and SWOT matrix. Based on the results of the study, in the IFAS matrix, product marketing that has not been maximized has the greatest influence whit a total score of 0,55, while in the EFAS matrix, the number of product requests that have the greatest influence is with a total score of 0,61. The results of the SWOT analysis show that the business position is in quadrant I, which means that the hybrid duck farming business in Besuki District has strong internal and external conditions. The development strategy that must be applied is the Growth Oriented Strategy (SO), where this strategy is made based on the company's mindset, namely by utilizing all forces to seize and take advantage of opportunities as much as possible. The strategies used are to increase the production of hybrid duck seedlings, utilize existing alternative feed, and maintain good relations between business actors.